Nutritional status and carbohydrate consumption frequency of preschoolers with diverse ethnic ancestry (Revista horizonte, 2022)
Introduction: The progressive increase of obesity in the Chilean school population is worrisome, both in ethnic and non-ethnic populations. The purpose of the study was to compare the dietary frequencies of the main macronutrient in the diet and the nutritional status of preschoolers belonging or not to native peoples of northern and southern Chile. Material and methods: There evaluated 166 preschoolers (90 San Pedro of Atacama and 76 Padre Las Casas) with an age in months of 61,05 + 6,60, with ethnic diversity and nationalities (Lickan antai, Mapuche, Aymaras, Peruanos, Bolivians and Chileans). They participated of the investigation of voluntarily. Information collected with regard to food frequency, ethnic ancestry, age, weight, height, circumference waist (Cw), and body mass index (BMI). Results: It was not found a increase trend to the prevalencia of overweight or obesity in any of the studied groups, at the same time, it can be outlined in the etnia mapuche a greatest frequency of food consumption of the groups of dairy, potatoes, legumes, and sugars; while for the etnia lickan antai, a high consumption of eggs, fruits and vegetables comparing these two ethnicities. Conclusion: concluded that there is exists a better quality of feeding in San Pedro of Atacama, however, it stand outed high prevalence of malnutricio?n for excess, while in Padre Las Casas, it stand outed the consumption of simple sugars. It is advisable to realize associations between genetic variants, ingestion of food and the nutritional status.